The Chosen Ummah By Muhammad 'Ali As-Shabuni (Interpretation in Q.S. Al-Baqarah 143 and Q.S. Ali ‘Imran 110) - M. Syarif Adi Pramana (Al-Wasatiyah: Journal of Religious Moderation, 2024)
Muslims today, in various aspects of life, are experiencing conditions or circumstances that are increasingly lagging behind Western nations. One of the causes is the division among Muslims themselves, which resulted in the emergence of several groups of thought that pose a danger and threat to the unity of the people. Religious moderation is present in society to prevent the emergence of extreme thinking and can create a living environment that is in harmony and peace. The book of Shafwah at-Tafasir by Muhammad ‘Ali as-Shabuni is used in this article because it uses light language and is easy to understand for readers. as-Shabuni is a scholar who pays attention to the condition of humankind. This article explores as-Shabuni's thoughts on the verses of religious moderation in this interpretation about The Chosen Ummah. The author uses a thematic method in describing the interpretation of as-Shabuni contained in the book Shafwah at-Tafasir. This article is qualitative research and uses library research in data retrieval to include information related to the discussion. The result of this study is that the interpretation as-Shabuni on Q.S. al-Baqarah: 143 is Allah made Muslims the best and chosen people, being in the Middle, not exaggerating and diminishing an act. They are witnesses to the day of judgment. In Q.S. Ali Imran:110, the chosen Ummah means a Ummah that benefits other Ummah, and this is intended for Muslims. In this case, the chosen people referred to by as-Shabuni are the best people (Muslims/Muhammad's Ummah), who do not add or subtract actions that result in being hated by God, people who are helpful because they command to do good and prevent the wicked and believe in Allah SWT, these actions are forms of religious moderation actions